The effectiveness of aloe vera compresses in preventing breast swelling and pain in post-partum - Getih Rahmawati; Irawati Indrianingrum; Ummi Kulsum (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast engorgement occurs due to increased milk production combined with irregular breastfeeding. This can be treated pharmacologically and non-pharmacologically by applying aloe vera compresses. Purpose: To analyse the effectiveness of aloe vera compresses on breast swelling and pain in postpartum mothers. Method: This study uses a quasi-experimental design, specifically a one-group pretest-posttest design. This study involved all patients in Desember 2025 was 104 mothers. The sample size was calculated using the finite population correction formula, resulting in a sample of 50 mothers. The instruments used to obtain research data were the Wong Baker Pain Rating Scale, Six Point Engorgement Scale (SPES), and aloe vera compress SOP. The data were analysed using the Wilcoxon test. Results: The results of the study explained that before the intervention, 32 (64%) respondents showed moderate breast engorgement and 33 (66%) respondents showed mild breast engorgement. Before the intervention, 38 (76%) respondents experienced moderate pain. After receiving the intervention, 37 (74%) respondents experienced mild pain. Conclusion: The results of the study indicate that aloe vera compresses are effective in reducing swelling (p=0.000) and breast pain (p=0.000) in postpartum mothers at Kartini General Hospital in Jepara. Suggestion: Future researchers are also advised to conduct studies by including a control group as a comparison group so that the differences between groups can be clearly distinguished.